Endometriosis-associated ovarian cancer is not a distinct clinical entity among young patients: A 12-year cohort study. Issue 5 (May 2020) - Cai, Yan; Yin, Jie; Jin, Ying; Li, Yan; Wu, Ming; Yang, Jiaxin; Huang, Huifang; Leng, Jinhua; Pan, Lingya
Abstract: Objectives: To investigate the clinicopathological features and prognostic value of endometriosis in young patients with ovarian endometrioid carcinoma (OEC) and ovarian clear cell carcinoma (OCCC). Methods: The medical files and clinical follow-up data of patients aged 40 years or younger with OEC or OCCC between January 2006 and December 2017 who had undergone complete surgical staging followed by systemic chemotherapy were retrospectively reviewed. Results: A total of 94 women were included in this study. Univariate analysis revealed that the progression-free survival (PFS) and overall survival (OS) rates of patients with endometriosis-associated ovarian carcinoma (EAOC) did not improve compared with those of patients without EAOC (5-year PFS: 80.0% vs. 75.9% and 5-year OS: 85.0% vs. 86.0%, respectively). Multivariate analyses confirmed that FIGO stage (II–IV), cytology-positive ascites or peritoneal washes and residual disease > 1 cm were independent predictors of PFS and that residual disease > 1 cm was the only predictor of OS. Conclusions: Endometriosis is not independently associated with the prognosis of OEC and OCCC among young patients. The intrinsic relationship between endometriosis and ovarian cancer warrants further investigation.